JIGSAW TECHNIQUE AND MIND MAPPING TECHNIQUE IN INCREASING STUDENTS VOCABULARY - Suhardi Suhardi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2015)
The objectives of this research were: (1) to find out te use of jigsaw technique significantly to improve students vocabulary of the second semester students at English department students of Cokroaminoto Palopo University (2) to find out te use of mind mapping technique significantly to improve students vocabulary of the second semester students at English department students of Cokroaminoto Palopo University (3) to find out which is technique and improve students vocabulary cooperative learning jigsaw technique and mind mapping technique. This research employed true experimental design. The population of this research was the second semester students of English department of Cokroaminoto University Palopo in academic year 2013/2014. The sample of this research was the second semester students in academic year 2013/2014 where consisted of 80 students. This research used cluster random sampling technique. The research data were collected by using two kinds of instrument namely: vocabulary test for the students. Data on the students vocabulary skills were analyzed by using idependent t-test. The results of the research were: (1) jigsaw technique can improve vocabulary of the students of English department of Cokroaminoto Palopo University, and (2) mind mapping technique can improve vocabulary of the students of English department of Cokroaminoto Palopo University (3) jigsaw technique and mind mapping technique were effective in learning vocabulary. It can be concluded that the jigsaw technique and mind mapping technique in the teaching process is effective to be implemented in improving the students vocabulary.